Effect of vitamin A administration in gamma-irradiated repair tissue as revealed by polarizing microscopy - Patricia Maria Usberti Vizioli; Mário Roberto Vizioli; Frab Norberto Boscolo; Solange Maria Almeida; Rosana Aramaki T Tanaka (Universidade Estadual de Campinas, 2015)
This work was performed in order to evaluate the effect of systemic administration of vitamin A against the damages caused by gamma radiation in rat repair tissue. It were used 48 animals. An incision was made in the dorsal region of the animals, which were separated into four experimental groups, composed of 12 animals each, as follows: Control group (CG) corresponding to the animals which were only submitted to the surgical procedure; Irradiated group (IG), composed by rats that have received 6 Gy of total body gamma irradiation 72 hours after the surgery; Vitamin A group (VAG), where the rats were treated with 15,000 UI of aqueous solution of vitamin A i.p. 48 hours after the wound infliction and Vitamin A irradiated group (VAIG) formed by animals treated in the same way as VAG but gamma-irradiated as IG. After the histological procedures, the repair tissues were observed at 4, 7, 14 and 21 days of development by means of qualitative and quantitative birefringence. The results pointed out to a very effective protection of the repair tissue performed by vitamin A against gamma irradiation.